Comparison of Immune Checkpoint Inhibitors between Older and Younger Patients with Advanced or Metastatic Lung Cancer: A Systematic Review and Meta-Analysis - Zhang, Leyin (Biomed Res Int, 2019)
OBJECTIVES: Despite the fact that it is widely acknowledged that immune checkpoint inhibitors (ICIs) rely on the presence of immune response to take their antitumor effect, little is known whether there is an influence exerted on the efficacy of ICIs based on patients' age. We performed a systematic review and meta-analysis to explore the efficacy of ICIs between younger and older patients. MATERIALS AND METHODS: We searched online database and major conference proceedings for randomized controlled trials (RCTs) published of ICIs and included RCTs that conducted subgroup comparisons of age with available combination of hazard ratios (HRs) and 95% confidence interval (95%CI). Subsequently, we figured out the pooled HR and 95%CI in younger and older patients with a random-effects model and evaluated the within-study heterogeneity by using subgroup, sensitivity, and meta-regression analysis. RESULTS AND CONCLUSION: A total of 12 eligible RCTs included in our study, which reported OS according to patients' age. The overall estimated random-effects for HR was 0.75 with 95% CI of 0.65-0.87 in younger arm versus 0.81 with 95% CI of 0.72-0.92 in older arm. ICIs can improve OS for patients with advanced or metastatic lung cancer when compared to controls, especially for those patients with NSCLC, anti-PD-1/PD-L1 inhibitors, non-squamous, Pembrolizumab or Atezolizumab used as well as subsequent-line setting, and the magnitude of benefit in OS had comparable efficacy in both younger and older arms using a cut-off of 65 yr. Conversely, we also drew a statically significant conclusion that older patients failed to acquire benefit from ICIs when subdivided with a further cut-off of 75 yr.